A study of C2 and V2 pathogenicity genes of Tomato curly stunt virus variants in tomato and Nicotiana benthamiana - Siviya, Lebogang Edith (My University, 2022)
Tomatoes are the second most important agricultural crop in the world. Due to selection and inbreeding, genetic variation in tomato is restricted, rendering the crop susceptible to disease and pest outbreaks. Tomatoes have been shown to be infected by a number of viruses. Tomato production is largely affected by begomovirus infections, with tomato yellow leaf curl virus (TYLCV) being the most destructive virus. Tomato yellow leaf curl disease (TYLCD) can have a massive impact on fruit yield, reducing the value of commercial tomato products. In 1997 a disease emerged in tomatoes that were planted in the Onderberg region of South Africa. Plants showed symptoms that were similar to those caused by tomato yellow leaf curl virus (TYLCV), namely leaf curling, yellowing and plant stunting. A new begomovirus species was found to cause these symptoms and the virus was named tomato curly stunt virus (ToCSV) Infection of tomato plants with ToCSV can lead to yield loses of up to 100% thus making ToCSV a major concern to the South African economy. A later study described two variants of ToCSV in South Africa, ToCSV_V30 (severe) and ToCSV_V22 (mild). Both variants have a genomic sequence identical to the Old World monopartite begomovirus with six Open Reading Frames(ORFs): V1 (CP), V2 (pre-coat protein), C1 (Rep), C2 (TrAP), C3 (REn), and C4 (REn). The aim of this study was to determine the importance of pathogenicity determinates C2 and V2 encoded by either ToCSV_V30 or ToCSV_V22 variants and their contribution to symptom phenotype or severity in tomato and Nicotiana benthamiana. To investigate if C2 and/or V2 are crucial for viral replication and viral DNA accumulation in tomato cv. Rooikhaki, mutational studies were carried out to determine the impact of mutations in the C2 and V2 ORFs of ToCSV variants. A chimeric infectious clone was produced by substituting the entire V2 region of ToCSV_V30 with that of the ToSCV_V22. Tomato cv. Rooikhaki was subsequently agroinfiltrated with the infectious clone, symptom scores (according to the disease severity index (DSI)) and viral load (using qPCR) were assessed. Plants inoculated with the chimeric infectious clone containing the V2 swap showed no significant differences in symptom severity when compared with symptoms induced by ToCSV_V30. However, when compared to wild-type ToCSV V30 and ToCSV V22, plants infected with the chimeric infectious clone, ToCSV_V30(V22V2aa1-116) (V2 swap), had higher levels of viral DNA. Relative viral load analyses indicated that the viral load of the swap was 5-fold and 3-fold higher at 21 dpi when compared to ToCSV_V30 and ToCSV_V22, respectively. These results suggest that disease severity is coupled to viral DNA levels in tomato plants infected with the V2 swap. The results indicated that the V2 swap did affect the levels of DNA replicated when compared to ToCSV_V22 and ToCSV_V30. In order to determine the function of C2 in pathogenicity, three C2 mutants were produced by substituting the amino acids (aa) in the severe ToCSV_V30 with the corresponding ones from the mild V22 variant; Mut 10 (ToCSV_V30(V22C2aa46)), Mut 9 (ToCSV_V30(V22C2aa48)), and Mut 7 (ToCSV_V30(V22C2aa109)). Plants infected with the C2 mutants developed symptoms that were similar to those produced by ToCSV_V30. Relative viral load analyses showed that the C2 mutants accumulated higher levels of DNA at 21 dpi when compared to the wild-type virus variants. Relative viral load of mut 7, mut 9 and mut 10 was 2.3-, 2.7-, and 2-fold, respectively, higher than ToCSV_V22 at 21 dpi, whereas the relative viral load change for the mutants were 4.38, 4,4 and 3.7-fold higher than ToCSV_V30. This suggests that the specific amino acids in the C2 region studied did affect viral DNA replication. By overexpressing C2 using a PVX expression vector, pGR107, the putative function of C2- encoded TrAP in pathogenicity by both mild and severe variants was studied in N. benthamiana. Plants inoculated with PXV expressing C2_V22 enhanced viral symptoms in inoculated leaves at 7dpi, however, plants inoculated with PVX expressing C2_V30 did not alter the symptoms induced by PVX. These results indicated that C2_V22 is a pathogenicity determinant in N. benthamiana. Intriguingly, plants inoculated with C2 expressed in PVX from both V30 and V22 showed symptom recovery in systemic leaves at 14 dpi and 28 dpi. RNA silencing has been found to be involved in the recovery of geminiviral symptoms. Therefore, to investigate if indeed ToCSV C2 was a suppressor of RNA silencing, the C2 of both severe and mild variants were cloned into pTRV VIGS vector and co-inoculated with GFP into transgenic N. benthamiana expressing GFP. Results indicated that ToCSV C2 weakly suppresses local RNA silencing in inoculated leaves at 4 dpi, however, C2 was unable to suppress systemic silencing in leaves at 14 and 28 dpi. These results have given an insight into the putative roles of C2 and V2 genes encoded by ToCSV variants showing different symptom severity and phenotype in N. benthamiana and tomato plants.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Molecular and Cell Biology to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: V2 pathogenicity genes; C2 pathogenicity genes; Tomatoes